(untitled) (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
The article explains that oil sludge has not been sufficiently studied when obtaining fixers for mobile sands and soil, which limits their use in road construction. Taking this into account, we analyzed two samples of oil sludge obtained from Dzharkurgan oil, physical and chemical indicators. Everyone knows that oil sludge is a hydrophobic substance that protects the effect of water on the formed crust of the fixer of mobile sands and soils. In laboratory conditions, the influence of the content of oil sludge on the fixing parameters of the resulting crust in mobile sands and soils was studied. It was revealed that the oil sludge of the Dzharkurgan oil treatment plant and the oil refinery can be used up to 20% in the composition of the obtained fixers of mobile sands and soils, and more than this amount greatly increases the mechanical strength of the formed crust, which negatively affects the phytomelioration of plants.